Dimenzioniranje lesenega mostu za pešce in kolesarje - Papinutti, Mitja (Gradbeni vestnik, 2011)
The subject of this paper is the constructional analysis and dimensio-ning of a bridge for pedestrians and cyclists. The special feature of the bridge is its ceiling and floor consisting of a CLT (Cross Laminated Timber) panel and four glued beams, designed according to ÖNORM B 4002 standards. In order to make the bridge appropriate for construction in Slovenia, it was necessary to adjust an existing bridge so that it would suit the Slovenian SIST EN 1995-1 standards. Using different static analysis gives us different results. The bridge has a span of 35 m and is suspended on two steal ties with the details that make the modelling of such bridges special.
Keywords: gradbena statika; leseni mostovi; statična analiza